2018
DOI: 10.1111/lam.13079
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of antimicrobial peptide AP2 using SUMO fusion partner technology inEscherichia coli

Abstract: Significance and Impact of the Study: AP2, an artificial mutant apidaecin (AP) peptide based on APs, has improved activities and may be regarded as a promising antibiotic alternatives. The secreted expression of antimicrobial peptide is of the greatest challenges because the antibacterial activity is not beneficial to the host. Our data suggest that the recombinant fusion strategy allows convenient high yield and easy purification of recombinant AP2. AbstractApidaecins (APs) are proline-rich antimicrobial pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Because previous efforts for expressing Api1b in bacteria involved its fusion to longer proteins or focused on minimizing its toxicity (24,25,27,29), we first tested whether the native PrAMP generated endogenously in Escherichia coli cells would retain its antibacterial activity and mechanism of action. We engineered two plasmid constructs containing synthetic api genes, under the control of the arabinose-inducible P BAD promoter, starting with the initiator AUG codon, followed by the codon-optimized sequence specifying the 18 amino acids of Api1b and ending with either UAG (pApi-UAG) or UGA (pApi-UGA) stop codons, decoded by RF1 or RF2, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because previous efforts for expressing Api1b in bacteria involved its fusion to longer proteins or focused on minimizing its toxicity (24,25,27,29), we first tested whether the native PrAMP generated endogenously in Escherichia coli cells would retain its antibacterial activity and mechanism of action. We engineered two plasmid constructs containing synthetic api genes, under the control of the arabinose-inducible P BAD promoter, starting with the initiator AUG codon, followed by the codon-optimized sequence specifying the 18 amino acids of Api1b and ending with either UAG (pApi-UAG) or UGA (pApi-UGA) stop codons, decoded by RF1 or RF2, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating curcumin into biopolymer-derived nanofibers may enhance its bioavailability at targeted sites with controlled release. 26,27 The release of curcumin from loaded electrospun fibers can be controlled by modulating the hydrophobicity/ hydrophilicity character of the fibers. 28 In this study, we aimed to fabricate dextran/zein electrospun fibers and investigate the effects of various zein concentrations on the properties of the hybrid electrospun fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The CTD is difficult to produce as IDPs are prone to proteolysis and aggregation [34,65–67]. Several studies have shown improvement in solubility and stability by fusing IDPs to a fusion partner, for example, SUMO [68,69], GST [70] or MBP [9]. We used the SUMO tag, which facilitates expression, solubility and subsequent purification with highly active and site-specific Ulp1 protease [37–39].…”
Section: Resultsmentioning
confidence: 99%